The contribution of community wisdom to conservation ecology. Issue 3 (25th April 2016) - Predavec, Martin; Lunney, Daniel; Hope, Ben; Stalenberg, Eleanor; Shannon, Ian; Crowther, Mathew S.; Miller, Indrie
Abstract: Scientists have traditionally collected data on whether a population is increasing, decreasing, or staying the same, but such studies are often limited by geographic scale and time frame. This means that for many species, understanding of trends comes from only part of their ranges at particular periods. Working with citizen scientists has the potential to overcome these limits. Citizen science has the added benefit of exposing citizens to the scientific process and engaging them in management outcomes. We examined a different way of using citizen scientists (instead of data collection). We asked community members to answer a question directly and thus examined whether community wisdom can inform conservation. We reviewed the results of 3 mail‐in surveys that asked community members to say whether they thought koala populations were increasing, decreasing, or staying the same. We then compared the survey results with population trends derived from more traditional research. Population trends identified through community wisdom were similar to the trends identified by traditional research. The community wisdom surveys, however, allowed the question to be addressed at much broader geographical scales and time frames. Studies that apply community wisdom have the benefit of engaging a broad section of the community in conservation research and education and therefore in the political process of conserving species.